Whole-blood global DNA methylation is increased in amyotrophic lateral sclerosis independently of age of onset. Issue 1 (March 2014) - Tremolizzo, Lucio; Messina, Paolo; Conti, Elisa; Sala, Gessica; Cecchi, Matteo; Airoldi, Luisa; Pastorelli, Roberta; Pupillo, Elisabetta; Bandettini Di Poggio, Monica; Filosto, Massimiliano; Lunetta, Christian; Agliardi, Cristina; et al.
Abstract ALS is a heterogeneous disease that is not well understood. Epigenetic rearrangements are important in complex disorders including motor neuron diseases. The aim of this study was to determine whether whole-blood DNA methylation (DNA MET %) is a potential modifier of age at onset in ALS. DNA MET % was measured as incorporation of [3H]dCTP following HpaII cut in 96 ALS patients and 87 controls, comprising: early-onset (< 55 years of age) and late-onset (> 74 years of age). Methionine (Met) and homocysteine (Hcy) plasma levels were assessed by liquid chromatography selected reaction monitoring coupled with isotope-dilution mass spectrometry. Results showed that DNA MET % was increased in ALS patients independently of age of onset. Compared to the other three groups, Hcy plasma levels were reduced in early-onset ALS patients but Met levels were similar. ROC analysis reported Met levels and DNA MET %, respectively, with a slight and moderate discriminative power. In conclusion, increased DNA MET % is a possible marker of epigenetic dysfunction in ALS independently of age of onset. Further studies dissecting biological determinants of phenotypic complexity in ALS may help in developing successful therapeutic strategies.